Survey of ICT knowledge based Agriculture Development System - H J. Shanthi (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
E-agriculture gives to applying new things to use ICTs in the country, with the main heart on agricultural. ICT in Agriculture provides a wide range of solutions to some farming ideas. The rising field focuses on the development of agricultural and rural advance through improved information and communication. This time, ICT is used as around all information and communication developments including Android mobiles, IOT devices, communication networking devices,  web services; this variety from original Internet-era technologies and sensors to other pre-accessible aids such as  TV, satellites, and radios. This technique continues to evolve in scope as new ICT applications continue to be harnessed in the agriculture industries. It involves the concept, development, design, application, and evaluation of novel ways to use ICTs in the rural domain, with the main focus on cultivation. This includes principles, norms, methods, and apparatus as well as the growth of personality and institutional capacity, and policy hold is all key mechanism of e-agriculture.